Audit Tenure as a Moderator in the Relationship Between Financial Distress, Profitability, and Audit Delay - I Ngurah Sudi Darma Yasa; Made Yenni Latrini (E-Jurnal Akuntansi, 2025)
This study investigates the influence of financial distress and profitability on audit delay, while also examining the moderating effect of audit tenure. Firm size is included as a control variable. The research focuses on energy sector firms listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The analysis is based on panel data comprising 270 firm-year observations, selected through purposive sampling, a non-probability sampling technique. Data were analyzed using STATA software, employing the Moderated Regression Analysis (MRA) approach with a fixed effects model to account for unobserved heterogeneity across firms. The empirical findings reveal that financial distress significantly increases audit delay, whereas profitability does not have a statistically significant effect. Furthermore, audit tenure moderates the relationship between financial distress and audit delay by attenuating its impact. However, rather than enhancing the effect of profitability on audit delay, audit tenure appears to diminish it.